Four new species of Selenops (Araneae, Selenopidae) and comments on the distribution of Afrotropical species - Corronca, José Antonio (Zootaxa, 2005)
Additional material of Selenopidae from the Afrotropical region was examined and four new species were found from Madagascar, Southern Africa and the Ivory Coast. Selenops ivohibe sp. nov. (female only) from Madagascar, S. tonteldoos sp. nov. (female only) from South Africa, S. onka sp. nov. (female only) from Namibia and Angola and S. jocquei sp. nov. (female only) from the Ivory Coast are described and illustrated. The global distribution of the genus Selenops from the Afrotropical region is illustrated based on all published data.